2021
DOI: 10.3390/cancers13215366
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Efficacy and Assessment of Tumor Response of Transarterial Chemoembolization in Neuroendocrine Liver Metastases: A 15-Year Monocentric Experience

Abstract: Background: transarterial chemoembolization (TACE) is an established treatment for neuroendocrine tumor (NET) liver metastases. The aim was to evaluate the long-term treatment efficacy of TACE for NET liver metastases, and correlate imaging response with survival. Methods: this IRB-approved, single-center, retrospective study evaluated all TACE procedures performed for NET liver metastases from 2003–2017 for imaging tumor response (RECIST and mRECIST), time to liver progression (TTLP), time to untreatable prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
(53 reference statements)
1
32
0
1
Order By: Relevance
“…The clinical predictive factors for poor response with liver-directed therapy’s efficacy include higher age [ 347 , 348 ] and poorer performance status (≥1) [ 349 , 350 , 351 ]. In terms of biomarkers, elevated pre-treatment levels of serum CgA [ 347 ], pancreastatin [ 342 , 352 ], bilirubin [ 353 ], alkaline phosphatase [ 354 , 355 ], and Child-Pugh score [ 351 , 355 ] are associated with worse OS post liver-directed therapies ( Table 5 ).…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical predictive factors for poor response with liver-directed therapy’s efficacy include higher age [ 347 , 348 ] and poorer performance status (≥1) [ 349 , 350 , 351 ]. In terms of biomarkers, elevated pre-treatment levels of serum CgA [ 347 ], pancreastatin [ 342 , 352 ], bilirubin [ 353 ], alkaline phosphatase [ 354 , 355 ], and Child-Pugh score [ 351 , 355 ] are associated with worse OS post liver-directed therapies ( Table 5 ).…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
“…Like the other treatment modalities, patients who experienced a radiological response to liver-directed therapies had better OS than non-responders [ 347 , 348 , 351 , 357 ]. It is also reported that an increasing number of TACE sessions is associated with better survival [ 347 , 352 ], which may be the case since patients with longer PFS are more likely to receive many sessions of TACE.…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
See 3 more Smart Citations